2017
DOI: 10.1002/jum.14290
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Oral Contrast‐Enhanced Transabdominal Ultrasound Imaging With Transverse Contrast‐Enhanced Computed Tomography in Preoperative Tumor Staging of Advanced Gastric Carcinoma

Abstract: The overall accuracy of transabdominal oral contrast-enhanced US was comparable with that of transverse contrast-enhanced CT for preoperative tumor staging of advanced gastric cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…Another study in 2017 demonstrated no significant difference in the overall accuracy of TAUS (86%, 36/42) and transverse contrast-enhanced CT (83%, 35/42, P > .999) (Fig. 4A) [20] . These findings suggested that TAUS could provide a satisfactory diagnosis with an accuracy similar to the CT method.…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…Another study in 2017 demonstrated no significant difference in the overall accuracy of TAUS (86%, 36/42) and transverse contrast-enhanced CT (83%, 35/42, P > .999) (Fig. 4A) [20] . These findings suggested that TAUS could provide a satisfactory diagnosis with an accuracy similar to the CT method.…”
Section: Resultsmentioning
confidence: 90%
“…4A). [20] These findings suggested that TAUS could provide a satisfactory diagnosis with an accuracy similar to the CT method. However, in the work of Cui et al, [19] the accuracy of TAUS was 72.9%, and that of the contrast-enhanced ultrasonography was 88.1% (P = .04) (Fig.…”
Section: Comparison Of Accuracy Between Taus and Other Techniquesmentioning
confidence: 83%
See 1 more Smart Citation
“…6 Ultrasonography is often the initial diagnostic method for GC; however, its accuracy is limited by the detection area and the operator’s skill level, and LN inflammation can be misdiagnosed as LN metastasis. 7 The diagnostic specificity of MRI is considered satisfactory in diagnosing LN metastasis; however, MRI takes time and may produce low-resolution images. 8 The accuracy of detecting LNs around the stomach and determining the N-stage by PET-CT is better than that by enhanced CT.…”
Section: Introductionmentioning
confidence: 99%
“…Lymph node (LN) metastasis around the stomach (Nos. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] is assessed before surgery. [3][4][5] Among these LNs, those located at station No.…”
Section: Introductionmentioning
confidence: 99%